Political cartoons as a vehicle of setting social agenda: the newspaper example - Sani, Iro; Abdullah, Mardziah Hayati; Abdullah, Faiz Sathi; Mohamad Ali, Afida (Canadian Center of Science and Education, 2012)
In recent years, the cartoons genre has gained considerable research interest across disciplines; for example, communication, media studies and health sciences. More so, cartoons serve as potent source of data used to study social phenomena. This paper aims at illustrating how political cartoons are used as a vehicle of setting social agenda in Nigerian newspapers to reorient and shape the public opinion through recurrent depictions mirroring current socio-political issues at a given period. The cartoons texts were excerpted from two major Nigerian newspapers, Daily Trust and Vanguard during the period 2007-2010. One-hundred cartoons were selected using purposive sampling technique. Fifty cartoons were taken from each newspaper magazine. Specifically, content analysis was used to identify the themes contained in the cartoons depictions. Qualitative method was used to analyze the cartoons through semiotic analysis. The analysis is mainly concerned with the interpretation of the sign system based on the connotation and denotation elements in the cartoons. The results indicated that 80% of the themes focused on substantive issues through which social agenda is set to reflect social practices in the Nigerian social political contexts. Also, the results showed that Nigerian political cartoons set social agenda by mainly encapsulating current and sensitive issues that people are much concerned about. Finally, the study has identified the lack of supportive and clearly defined theoretical background in analyzing political cartoons as a major problem in previous cartoons research. Thus, this paper contributes to the cartoon research by offering theoretical insight to the cartoon genre through agenda setting theory of media effect.